Quantitative analysis of tiropramide in human blood by gas chromatography with nitrogen-phosphorus detector - Kwon, OS; Park, YJ; Ryu, JC; Chung, YB (PHARMACEUTICAL SOC KOREA, 2003)
The analytical method of antispasmodic agent tiropramide {(+/-)alpha-(benzoylamino)-4-[2-(diethylamino)ethoxy]-N,N-dipropylbenzenepropanamide hydrochloride) was developed by gas chromatography/nitrogen-phosphorus detector (GC/NPD) in human plasma. Two kinds of tiropramide tablets were orally administered to volunteers by Latin square crossover design, and blood was withdrawn as designed schedule. The plasma of 1 mL was loaded on Sep-pak C-18 cartridge and eluted with methanol after washing with 30% methanol. The residue dissolved in 100 muL of methanol after evaporation was analyzed by GC/NPD. Precision (CV%) of intra-day was located within 2.6% and accuracy was less than 9.7%. Inter-day precision was below 8.7% and accuracy was relatively good as less than 14%. Plasma samples obtained from human volunteers were analyzed for the determination of tiropramide concentration by using this method. The method was sensitive, rapid and suitable enough to be applied for pharmacokinetic and bioequivalence studies of tiropramide in human volunteers.